From Model Housing to Possible Housing, the Strange Case of the Prolet Settlement, Skopje - Bakalchev, V., Tasic, S., Hadzi-Pulja, M., Bakalchev, M. (My University, 2017)
The question of housing has surfaced in a dramatic manner in the period of social, political and cultural transition that we witnessed in the 1990-s, the effects and patterns of which still characterize the Eastern European countries. The socially based housing has transformed into private, compartmentalized housing, and the standard program has transformed into one of individual excessive needs. For many, this has been a negative trend of physical and social destruction or degradation of the established system, while on the other hand it has provided us with a model for an informal, affordable housing. In the example of a housing settlement constructed in the post-World War II reconstruction of Skopje, we shall observe the process of transformation in the key political and social periods, through typological conversion at the level of housing units as well as residential buildings or groups. Can we observe and discover in this predominantly deviant procedure, certain transformative models as examples of affordable housing? What can the dual notion of primary purpose and contemporary adaptation teach us about housing amid plan and action, perpetuity and transience? In the case of the Prolet Settlement we will attempt to find the possible models of affordable housing today.
Pavilion of SARP Association of Polish Architect, Warsaw, June 2017
Keywords: affordable housing, transition, typological transformation